The role of pre operative serum LDH and D-dimers in predicting intestinal necrosis - D., Manjunath B.; K., Avinash; G. S., Abdul Razack; R., Harindranath H.; V. H., Ashwath; Ali, Mohammed Arafath; T., Kavya (International Surgery Journal, 2019)
Background: To study the role of serum LDH and D-Dimers in predicting intestinal necrosis, to correlate with bowel viability preoperatively and to determine the aetiology for intestinal necrosis due to Mesenteric Ischaemia or any other causes. Methods: A prospective study conducted in 100 patients admitted in the Dept of General Surgery, Victoria Hospital, Bangalore Medical College for a period of one year. Results: In our study out of 100 patients 44 patients had elevated serum LDH which is 44% and among those 44 patients, 39 patients found to have bowel gangrene which is about 88%. Out of 100 patients 9 patients had elevated D-dimer levels which are 9% and among those 9 patients, 6 were suspected of mesenteric ischaemia and all patients had bowel gangrene which 100%. Conclusions: The pre operative estimation of serum LDH levels in patients presenting with features of acute abdomen helps in identifying the patients with risk of intestinal ischemia and gangrene at the earliest, facilitating early intervention and helping in reduction of morbidity and mortality due to bowel gangrene. Detection of serum D-dimer could not help to differentiate patient with mesenteric ischaemia from those with other causes of bowel necrosis but certainly all cases of mesenteric ischaemia had elevated D-dimer levels. The application of serum LDH and D-dimers in acute abdomen or suspected cases of bowel necrosis will give an important clue regarding the pathology and severity of the disease.